Mengungkap Konstruksi Identitas Sosial dalam Lirik Lagu Daerah “Wuna Nokokasinta” Karya Wilmar Pater - Hadirman, Hadirman (YASIN, 2025)
This study aims to analyze the relationship between signifier and signified, denotation and connotation structures, and the construction of social identity reflected in the lyrics of regional songs and Wuna Nokokasinta by Wilmar Pater. Using Roland Barthes' semiotic theory, this study reveals the symbolic meaning and identity construction contained in the lyrics of popular regional songs as a representation of the culture of the Muna people. The method used is a descriptive qualitative method with a text analysis approach. Data were obtained through a documentation study from the Nawir Musik Channel. The study results show that the lyrics of the Wuna Nokokasinta song reflect the close relationship between the Muna people and their ancestral land, religiosity, identity, cultural direction, and the value of harmony. The denotative meaning in the lyrics reflects a concrete description of the land of Muna as a blessed and beloved land. At the connotation level, these songs express the values ​​of collectivity, love for the homeland, solidarity, and respect for ancestral traditions. In addition, the symbolism in the lyrics emphasizes the social identity of the Muna people as a community that upholds the values ​​of togetherness, social justice, and gratitude for the blessings they have. This study concludes that the lyrics of Muna regional songs are not only a medium of artistic expression, but also a means of preserving the noble values ​​of culture that strengthen the social identity of its people. The songs function as a collective reminder of the importance of maintaining social harmony and as an emotional bond between the Muna people and their homeland.